2011
DOI: 10.1016/j.trf.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotypes associated with vehicle driving among French preadolescents and adolescents

Abstract: Gender differences in accidentology, notably on roads, are well documented and current research in social psychology tends to explain these differences by gender stereotypes, notably the association of risk-taking with social expectations concerning masculinity. To date, however, little research has explored gender stereotypes associated with vehicle driving. Beliefs about driving by men and women, as well as the effect of the age and gender of the perceiver, were explored using the free association method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 92 publications
2
27
0
4
Order By: Relevance
“…The disparities between the sexes observed in our study are a common global finding and sex-related stereotypes about risk-taking and risk perception while driving have an influence on this phenomenon [17,18]. In urban areas of Mexico, male automobile drivers are more likely to be involved in alcohol-impaired driving and less likely to use seatbelts [19,20].…”
Section: Discussionmentioning
confidence: 92%
“…The disparities between the sexes observed in our study are a common global finding and sex-related stereotypes about risk-taking and risk perception while driving have an influence on this phenomenon [17,18]. In urban areas of Mexico, male automobile drivers are more likely to be involved in alcohol-impaired driving and less likely to use seatbelts [19,20].…”
Section: Discussionmentioning
confidence: 92%
“…Historically, female drivers were characterized as lacking the emotional stability and psycho-emotional qualities required to successfully maneuver an automobile (Albert, 1999;Berger, 1986). More recent research has revealed that the belief that women are bad drivers stems from women's perceived inattention and carelessness (Granié & Papafava, 2011;Lawrence & Richardson, 2005). Experimental investigation of the extralegal factors impacting perceptions of drivers involved in auto accidents has revealed that female drivers (vs. male drivers) are more likely to be perceived as lacking driving skill, poor judges of speed, distracted, lacking attention, and generally confused about appropriate driving rules and behaviors (Glendon et al, 1996;Lawrence & Richardson, 2005).…”
Section: Female Driver Stereotypesmentioning
confidence: 99%
“…The stereotype that women are bad drivers is pervasive: Documented endorsement of this stereotype is found in multiple countries around the world (e.g., United States, France, Australia; Berger, 1986;Glendon, Dorn, Davies, Matthews, & Taylor, 1996;Granié & Papafava, 2011;Yeung & von Hippel, 2008). Specifically, compared to men, women tend to be perceived as more careless behind the wheel (Lawrence & Richardson, 2005), as having less driving skill (Glendon et al, 1996), and having poorer parking abilities (Derks, Scheepers, Van Laar, & Ellemers, 2010;Wolf et al, 2010).…”
mentioning
confidence: 99%
“…Furthermore, the role of demographic factors (age, gender, education, etc. ) and the involvement of certain individuals in accidents have been investigated in several studies (Dobson et al, 1999;Granié and Papafava, 2011;Oltedal and Rundmo, 2006;Parker et al, 2000). In another study Kim et al (1995) showed that driver behavior and either alcohol or drug use act as a mediated link between driver's age and sex and both accident type and injury severity.…”
Section: Introductionmentioning
confidence: 99%